Genome-wide linkage and association of novel genes and pathways with type 2 diabetes in Italian families - Mutaz Amin; Claudia Gragnoli (Aspects of Molecular Medicine)
Background: Type 2 diabetes mellitus (T2D) stands as one of the most prevalent chronic diseases globally, posing substantial health and economic burdens on society. Within the spectrum of T2D, familial cases emerge as a distinct entity characterized by a strong familial clustering of the disease. This phenomenon has long suggested that genetics contributes substantially to T2D susceptibility, motivating extensive research into the genetic determinants of familial T2D. Methods: We recruited 212 multigenerational Italian families with multiple cases of T2D. The families were genotyped using genomic array (≥ 600k) derived from the UK Biobank Axiom Array platform. Informative markers were tested via Pseudomarker for linkage to and linkage disequilibrium (i.e., linkage joint to association) with T2D across the following models: dominant with complete penetrance (D1), dominant with incomplete penetrance (D2), recessive with complete penetrance (R1), and recessive with incomplete penetrance (R2). Results: We identified a total of 566 variants reaching genome-wide significant (P < 0.00005) linkage and/or association to/with the risk of T2D in Italian families. Of the 355 genes identified in our study, 341 (96%) are novel and have not been reported with T2D or any of its related phenotypes (i.e., obesity, metabolic syndrome, insulin resistance, polycystic ovary syndrome, and hyperglycemia). Conclusion: Our study constitutes the first familial T2D-linkage and association study in the Italian population. However, the functional relevance of the novel variants and genes reported in our study remains to be explored.